2005
DOI: 10.1126/science.1105486
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an Algal Morphogenesis Inducer from a Marine Bacterium

Abstract: Ulva and Enteromorpha are cosmopolitan and familiar marine algal genera. It is well known that these green macroalgae lose their natural morphology during short-term cultivation under aseptic conditions and during long-term cultivation in nutrient-added seawater and adopt an unusual form instead. These phenomena led to the belief that undefined morphogenetic factors that were indispensable to the foliaceous morphology of macroalgae exist throughout the oceans. We characterize a causative factor, named thallusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
177
1
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(204 citation statements)
references
References 4 publications
10
177
1
10
Order By: Relevance
“…Although Bacteroidetes bacteria regulate morphogenetic processes in such diverse lineages as animals, red algae, and green algae (Provasoli and Pintner 1980; Matsuo et al 2005; Mazmanian et al 2005), the bacterially produced chemical cues that regulate most of these partnerships remain obscure. The limited phylogenetic distribution of bacteria capable of inducing rosette colony development suggested that A. machipongonensis and its close relatives may produce a characteristic molecule that could be identified biochemically.…”
Section: Resultsmentioning
confidence: 99%
“…Although Bacteroidetes bacteria regulate morphogenetic processes in such diverse lineages as animals, red algae, and green algae (Provasoli and Pintner 1980; Matsuo et al 2005; Mazmanian et al 2005), the bacterially produced chemical cues that regulate most of these partnerships remain obscure. The limited phylogenetic distribution of bacteria capable of inducing rosette colony development suggested that A. machipongonensis and its close relatives may produce a characteristic molecule that could be identified biochemically.…”
Section: Resultsmentioning
confidence: 99%
“…17 An algal morphogenesis inducer, thallusin, produced by a marine bacterium, has a terpenoid skeletal structure that is the enantiomer of that produced by fungi or plants. [18][19][20] As the absolute stereochemistry must be regulated by the three dimensional conformation of the biosynthetic enzyme, comparative research of the enzymes in Streptomyces and fungi is of much interest.…”
Section: Preparation Of Germicidinsmentioning
confidence: 99%
“…Recently, it was shown that IAA, synthesized by a Sulfitobacter species using tryptophan produced by the diatom Pseudonitzschia multiseries, promotes the growth of the latter (Amin et al 2015). Growth-stimulating phytohormonelike substances such as thallusin and other compounds still to be identified have been also isolated from Monostroma and Ulva (Matsuo et al 2005. Similarly, the brown alga Ectocarpus was shown to interact with an alphaproteobacterium that harbors several proteins thought to be involved in the synthesis of algal hormones such as auxins and cytokinins (Dittami et al 2014).…”
Section: Endogenous Signalingmentioning
confidence: 99%